Lithium ion solid electrolyte as well as preparation method and application thereof

By adopting a core-shell structure in the lithium-ion solid electrolyte, combining lithium-rich NASICON type and the second NASICON type solid electrolyte, the problem of hydrolysis of traditional lithium-ion solid electrolytes in a low dew point environment is solved, and the electrolyte with high stability, low water absorption and high ionic conductivity is achieved, which improves the electrochemical performance and cycle life of the battery.

CN119833731APending Publication Date: 2025-04-15CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411016829.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The traditional NASICON type lithium-ion solid electrolyte absorbs moisture in a low dew point environment and leads to hydrolysis, affecting the reliability and conductivity of the battery separator. It will destroy its stability when removing moisture by vacuum baking and increase production costs.

Method used

The lithium-ion solid electrolyte with a core-shell structure has a core of lithium-rich NASICON type solid electrolyte, and the coating is a second NASICON type solid electrolyte. It is prepared by a sintering process to ensure that the electrolyte has high ionic conductivity, low water absorption and stability.

Benefits of technology

It improves the stability and ionic conductivity of lithium-ion solid electrolytes, reduces water absorption, extends the cycle life and electrochemical performance of the battery, reduces the preparation cost, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833731A_ABST
    Figure CN119833731A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion solid-state electrolyte and a preparation method and application thereof.The lithium ion solid-state electrolyte comprises an inner core and a coating layer coating the surface of the inner core, the inner core comprises a lithium-rich NASICON type solid-state electrolyte, the coating layer comprises a second NASICON type solid-state electrolyte, the chemical formula of the second NASICON type solid-state electrolyte is LiM2 (PO4) 3, m is at least four tetravalent metal elements. The lithium ion solid electrolyte provided by the invention is high in ionic conductivity and low in water absorption, and can provide the electrochemical performance and the cycle life of a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to lithium-ion solid electrolytes and preparation methods and applications thereof. Background Art

[0002] At present, sodium superion conductor (NASICON) type lithium ion solid electrolyte can improve the electrochemical performance of batteries due to its low price, high ion conductivity and high stability. Although the traditional NASICON type lithium ion solid electrolyte can exist stably in an air environment, it has a strong affinity for water and absorbs a large amount of water in a low dew point environment, causing the NASICON type lithium ion solid electrolyte to hydrolyze. When used in a battery separator, it will cause the reliability and conductivity of the battery separator to decrease. In the related art, the moisture in the sodium superion conductor solid electrolyte can be removed by vacuum baking, but vacuum baking will destroy the stability of the NASICON type lithium ion solid electrolyte, aggravate the battery discharge phenomenon, cause the battery short circuit, and increase the production cost, which is not conducive to industrial production. Therefore, a lithium ion solid electrolyte with low water absorption, high stability and high ion conductivity is needed. Summary of the invention

[0003] In view of this, the present application provides a lithium-ion solid electrolyte and a preparation method and application thereof. The lithium-ion solid electrolyte with a core-shell structure in the present application has high stability, high ionic conductivity and low water absorption, which is beneficial to improving the electrochemical performance and cycle life of the battery, and solves the problem that the traditional sodium superion conductor type lithium-ion solid electrolyte has a strong affinity for water, resulting in a decrease in the electrochemical performance and cycle life of the battery.

[0004] In a first aspect, the present application provides a lithium-ion solid electrolyte, comprising a core and a coating layer coated on the surface of the core, the core comprising a lithium-rich NASICON-type solid electrolyte, the coating layer comprising a second NASICON-type solid electrolyte, the chemical formula of the second NASICON-type solid electrolyte being LiM2(PO4)3, wherein M is at least four tetravalent metal elements.

[0005] Optionally, the metal element is selected from Ti, Ge, Mn, In, Te, Sc, Y, V, Cr, Hf, Ce, Zr, Pb and Sn.

[0006] Optionally, among the at least four tetravalent metal elements, the molar percentage of each of the metal elements is greater than or equal to 10%.

[0007] Optionally, the lithium-rich NASICON solid electrolyte includes Li 1+a Al a Ti 2-a (PO4)3 and Li1+y Al y Ge 2-y (PO4)3, wherein a is 0.1-0.5 and y is 0.1-0.5.

[0008] Optionally, the configuration entropy of the second NASICON solid-state electrolysis is greater than or equal to 10.73 J / (mol·K).

[0009] Optionally, the coating layer has a thickness of 5nm-30nm, and the D50 particle size of the core is 100nm-5μm.

[0010] Optionally, in the lithium-ion solid electrolyte, the mass percentage of the coating layer is 5%-30%, and the mass percentage of the core is 70%-95%.

[0011] Optionally, the ionic conductivity of the lithium ion solid electrolyte is greater than or equal to 4.8×10 -4 S / cm.

[0012] Optionally, the water absorption of each gram of the lithium-ion solid electrolyte is less than or equal to 0.25 wt %.

[0013] The core of the lithium-ion solid electrolyte provided in the present application includes a lithium-rich NASICON-type solid electrolyte with excellent conductivity, and the coating layer includes a second NASICON-type solid electrolyte with low water absorption, so that the lithium-ion solid electrolyte has both high ionic conductivity and low water absorption.

[0014] In a second aspect, the present application provides a method for preparing a lithium ion solid electrolyte, comprising:

[0015] The metal element source, lithium source, phosphorus source and core material solution are mixed and sintered to obtain a lithium ion solid electrolyte.

[0016] Optionally, the solid content of the core material solution is 5%-40%.

[0017] Optionally, the molar ratio of the lithium element in the lithium source, the phosphorus element in the phosphorus source and the metal element in the metal element source is (0.4-0.5):(1.4-1.6):1.

[0018] Optionally, the metal element source includes one or more of metal nitrates, metal organic salts and metal oxides.

[0019] Optionally, the sintering temperature is 700°C-900°C.

[0020] The preparation method of the lithium ion solid electrolyte provided in the present application is novel, the preparation process is simple, and the prepared product has excellent performance.

[0021] In a third aspect, the present application provides a battery, comprising the lithium ion solid electrolyte described in the first aspect or the lithium ion solid electrolyte prepared by the preparation method described in the second aspect.

[0022] The battery provided in this application has excellent electrochemical performance and long cycle life, which is conducive to industrial application.

[0023] In a fourth aspect, the present application provides an electrical device, wherein the electrical device comprises the battery described in the third aspect.

[0024] The electrical equipment provided in this application has excellent comprehensive performance, greatly improved safety performance, and strong product competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0026] Figure 1 A schematic diagram of the cross-sectional structure of a lithium-ion solid electrolyte provided in one embodiment of the present application;

[0027] Figure 2 X-ray diffraction patterns of the lithium-ion solid electrolytes prepared in Examples 1-7 and Comparative Example 1 of the present application.

[0028] Figure 3 This is the electrochemical impedance spectrum of the lithium-ion solid electrolyte sheet prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0030] See also Figure 1, is a schematic diagram of the cross-sectional structure of a lithium-ion solid electrolyte provided in one embodiment of the present application, the lithium-ion solid electrolyte 100 includes a core 11 and a coating layer 12 coated on the surface of the core 11, the core 11 includes a lithium-rich NASICON-type solid electrolyte, the coating layer 12 includes a second NASICON-type solid electrolyte, the chemical formula of the second NASICON-type solid electrolyte is LiM2(PO4)3, and M is at least four tetravalent metal elements. In the present application, the core includes a lithium-rich NASICON-type solid electrolyte, which can improve the ionic conductivity of the lithium-ion solid electrolyte; the coating layer includes a second NASICON-type solid electrolyte, in which a tetravalent metal element is used as a doping metal element, which not only maintains the high ionic conductivity of the lithium-ion solid electrolyte, but also avoids the charge imbalance caused by the different charges of the metal elements, thereby introducing too many lithium atoms and reducing the water absorption of the second NASICON-type solid electrolyte; the core and the coating layer both include a sodium superion conductor solid electrolyte, which has good interface compatibility, and the coating layer can block the contact between the core and water, reduce the affinity of the lithium-ion solid electrolyte for water, and improve the stability of the lithium-ion solid electrolyte. When used in a battery, the lithium-ion solid electrolyte with low water absorption can be baked without treatment, which reduces the preparation cost of the battery and is conducive to the industrial production of the battery. The lithium-ion solid electrolyte provided in the present application has both high ionic conductivity and low water absorption, which is conducive to improving the cycle life and electrochemical performance of the battery.

[0031] In one embodiment of the present application, the core 11 is a lithium-rich NASICON solid electrolyte, and its chemical formula may include but is not limited to Li 1+a Al a Ti 2-a (PO4)3 and Li 1+y Al y Ge 2-y (PO4)3, wherein a is 0.1-0.5, y is 0.1-0.5. Li 1+x Al x Ti 2-x (PO4)3 and Li 1+y Al y Ge 2-y (PO4)3 contains two or more elements, such as Al, Ti and Ge. A small amount of Al is doped into LATP and LAGP. In the crystal structure, Al 3+ Occupies Ti 4+ Or Ge 4+ sites, resulting in lattice expansion and charge imbalance. In order to balance the crystal charge, additional Li + , improve the structural stability of lithium-ion solid electrolytes, Li +The entry of lithium ions increases the ion diffusion channel of lithium ions, thereby greatly improving the ion conductivity of the lithium ion solid electrolyte. Specifically, x can be but not limited to 0.1, 0.2, 0.3, 0.4 or 0.5, and y can be but not limited to 0.1, 0.2, 0.3, 0.4 or 0.5. In one embodiment of the present application, the lithium-rich NASICON solid electrolyte can be Li 1.1 Al 0.2 Ti 1.8 (PO4)3. In another embodiment of the present application, the lithium-rich NASICON solid electrolyte may be Li 1.4 Al 0.4 Ge 1.6 (PO4)3.

[0032] In one embodiment of the present application, in the lithium ion solid electrolyte, the mass percentage of the core 11 is 70%-95%, and the appropriate mass of the core 11 can improve the ionic conductivity of the lithium ion solid electrolyte. Specifically, in the lithium ion solid electrolyte, the mass percentage of the core 11 can be, but not limited to, 70%, 75%, 80%, 85%, 90% or 95%, etc. In one embodiment of the present application, in the lithium ion solid electrolyte, the mass percentage of the core 11 can be 70%-85%. In another embodiment of the present application, in the lithium ion solid electrolyte, the mass percentage of the core 11 can be 80%-95%.

[0033] In one embodiment of the present application, the D50 particle size of the kernel 11 is 100nm-5μm. Suitable kernel D50 particle size can improve the energy density of lithium-ion solid electrolytes and enhance the electrochemical performance of batteries. Specifically, the D50 particle size of the kernel can be, but is not limited to, 100nm, 500nm, 1μm, 2μm, 3μm, 4μm or 5μm, etc. In one embodiment of the present application, the D50 particle size of the kernel can be 100nm-3μm. In another embodiment of the present application, the D50 particle size of the kernel can be 2μm-5μm.

[0034] In the present application, the chemical formula of the second NASICON-type solid electrolyte is LiM2(PO4)3, where M is at least four tetravalent metal elements. Although the ionic conductivity of the lithium-ion solid electrolyte is improved in the core, the introduction of too many lithium ions increases the affinity of the core for water. The tetravalent metal elements in the second NASICON-type solid electrolyte can avoid the introduction of additional lithium atoms due to charge imbalance, and the surface lithium content is low, and the affinity for water is low. At the same time, it blocks the contact between the core and water, thereby improving the stability of the lithium-ion solid electrolyte; multiple metal elements can cause lattice distortion of the sodium superion conductor structure, resulting in the overlap of the energy level distribution of lithium atoms at different points, so that lithium ions penetrate between different lattice sites under extremely low activation energy conditions, thereby improving the ionic conductivity of the lithium-ion solid electrolyte. Specifically, the metal element can be selected from, but not limited to, Ti, Ge, Mn, In, Te, Sc, Y, V, Cr, Hf, Ce, Zr, Pb and Sn. In one embodiment of the present application, the metal element can be Ti, Ge, Mn and V. In another embodiment of the present application, the metal element may be Ti, Ge, Sn, Zr and Hf, which can further improve the ionic conductivity of the lithium-ion solid electrolyte and reduce its water absorption.

[0035] In one embodiment of the present application, among the at least four tetravalent metal elements, the molar percentage of each metal element is greater than or equal to 10%. In some embodiments, when the second NASICON-type solid electrolyte has four metal elements, the four metal elements can be in an equal molar ratio, the molar percentage of each metal element is 25%, the molar number of each metal element is 0.5, and the chemical formula of the second NASICON-type solid electrolyte can be LiTi 0.5 Zr 0.5 Mn 0.5 Sn 0.5 (PO4)3; In some other embodiments, the second NASICON-type solid electrolyte has four metal elements, the four metal elements may be in non-equivalent molar ratios, the minimum molar percentage of each metal element is greater than or equal to 15%, the molar percentage of the metal element may be 10%, 15%, 20%, 30% and 35%, the molar number of the metal element may be 0.3, 0.4, 0.6 and 0.7, and the chemical formula of the second NASICON-type solid electrolyte may be LiTi 0.3 Zr 0.4 Mn 0.6 Sn 0.7 (PO4)3. In another embodiment, the second NASICON type solid electrolyte has five metal elements, which may be Ti, Ge, Sn, Zr and Hf. The chemical formula of the second NASICON type solid electrolyte is LiTi 0.4 Zr 0.4 Hf 0.4 Sn0.4 Ge 0.4 (PO4)3 can further improve the ionic conductivity of lithium-ion solid electrolytes and reduce their water absorption.

[0036] In one embodiment of the present application, the configuration entropy of the second NASICON-type solid electrolyte is greater than or equal to 10.73 J / (mol·K), which can improve the stability of the second NASICON-type solid electrolyte. The calculation formula of the configuration entropy is: Where R is 8.314, N is the number of metal elements in the second NASICON solid electrolyte, x i is the molar percentage of a certain metal element, x i Greater than or equal to 10%. Specifically, the configuration entropy of the second NASICON solid electrolyte may be, but is not limited to, greater than or equal to 10.73 J / (mol·K), greater than or equal to 10.8 J / (mol·K), greater than or equal to 10.9 J / (mol·K), greater than or equal to 11 J / (mol·K), greater than or equal to 11.2 J / (mol·K), greater than or equal to 11.4 J / (mol·K), or greater than or equal to 11.5 J / (mol·K), etc. In one embodiment of the present application, the configuration entropy of the second NASICON solid electrolyte may be greater than or equal to 11 J / (mol·K). In another embodiment of the present application, the configuration entropy of the second NASICON solid electrolyte may be greater than or equal to 11.2 J / (mol·K).

[0037] In one embodiment of the present application, in the lithium-ion solid electrolyte, the mass percentage of the coating layer 12 is 5%-30%, and an appropriate amount of the coating layer 12 can reduce the water absorption of the lithium-ion battery. Specifically, in the lithium-ion solid electrolyte, the mass percentage of the coating layer 12 can be but not limited to 5%, 10%, 15%, 20%, 25% or 30%, etc. In one embodiment of the present application, in the lithium-ion solid electrolyte, the mass percentage of the coating layer 12 can be 5%-20%. In another embodiment of the present application, in the lithium-ion solid electrolyte, the mass percentage of the coating layer 12 is 15%-30%.

[0038] In one embodiment of the present application, the coating layer 12 has a thickness of 5nm-30nm, which can improve the structural stability of the lithium ion solid electrolyte. Specifically, the thickness of the coating layer 12 can be, but is not limited to, 5nm, 10nm, 15nm, 20nm, 25nm or 30nm. In one embodiment of the present application, the thickness of the coating layer 12 can be 5nm-20nm. In another embodiment of the present application, the thickness of the coating layer 12 can be 15nm-30nm.

[0039] In one embodiment of the present application, the ionic conductivity of the lithium ion solid electrolyte is greater than or equal to 4.8×10 -4 S / cm, and suitable ionic conductivity is beneficial to improving the rate performance and cycle performance of the battery. Specifically, the ionic conductivity of the lithium ion solid electrolyte can be, but is not limited to, greater than or equal to 4.8×10 -4 S / cm, greater than or equal to 4.9×10 - 4 S / cm, greater than or equal to 5×10 -4 S / cm, greater than or equal to 5.5×10 -4 S / cm, greater than or equal to 6.5×10 -4 S / cm or greater than or equal to 6.7×10 -4 S / cm, etc. In one embodiment of the present application, the ionic conductivity of the lithium ion solid electrolyte may be greater than or equal to 5.5×10 -4 In another embodiment of the present application, the ionic conductivity of the lithium ion solid electrolyte may be greater than or equal to 6×10 -4 S / cm.

[0040] In one embodiment of the present application, the water absorption of each gram of lithium ion solid electrolyte is less than or equal to 0.25wt%. The water absorption of the lithium ion solid electrolyte is small, which improves the stability of the battery and reduces the preparation cost of the battery. Specifically, the water absorption of each gram of lithium ion solid electrolyte can be, but is not limited to, less than or equal to 0.25wt%, less than or equal to 0.22wt%, less than or equal to 0.18wt%, less than or equal to 0.15wt% or less than or equal to 0.13wt%, etc. In one embodiment of the present application, the water absorption of each gram of lithium ion solid electrolyte can be less than or equal to 0.19wt%. In another embodiment of the present application, the water absorption of each gram of lithium ion solid electrolyte can be less than or equal to 0.16wt%.

[0041] The present application also provides a method for preparing a lithium ion solid electrolyte, comprising: mixing a metal element source, a lithium source, a phosphorus source and a core material solution, and sintering to obtain a lithium ion solid electrolyte. The preparation method provided by the present application is novel, the preparation process is simple, the preparation cost is low, the prepared lithium ion solid electrolyte has low affinity for water, high stability, good ion conductivity, is conducive to the storage and transportation of lithium ion solid electrolytes, and improves the electrochemical performance and cycle life of the battery.

[0042] In one embodiment of the present application, the solid content of the core material solution is 5%-40%, and an appropriate amount of solid content can improve the ionic conductivity of the lithium ion solid electrolyte. Specifically, the solid content of the core material solution can be, but is not limited to, 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%, etc. In one embodiment of the present application, the solid content of the core material solution can be 5%-25%. In another embodiment of the present application, the solid content of the core material solution can be 20%-40%.

[0043] In one embodiment of the present application, the metal element source includes one or more of metal nitrates, metal organic salts and metal oxides. Specifically, the metal nitrate may include, but is not limited to, one or more of zirconium nitrate (Zr(NO3)4·5H2O), cerium nitrate (Ce(NO3)4·5H2O), manganese nitrate (Mn(NO3)4), tin nitrate (Sn(NO3)4), molybdenum nitrate (Mo(NO3)4) and lead nitrate (Pb(NO3)4); the metal organic salt may include, but is not limited to, one or more of metal organic alkoxides; the metal oxide may include, but is not limited to, one or more of TiO2, GeO2, MnO2, VO2, HfO2, SnO2 and PbO2. In one embodiment of the present application, when a lithium ion solid electrolyte is prepared by a solid phase method, the metal element source may be a metal oxide. In another embodiment of the present application, when a lithium ion solid electrolyte is prepared by a liquid phase method, the metal element source may be a metal nitrate and a metal organic salt.

[0044] In one embodiment of the present application, the lithium source provides lithium elements to form a lithium ion solid electrolyte, which is beneficial to improve the conductivity of the electrolyte. Specifically, the lithium source may include, but is not limited to, one or more of LiOH·H2O, Li2CO3, and LiNO3. In one embodiment of the present application, the lithium source may be Li2CO3. In another embodiment of the present application, the lithium source may be LiNO3.

[0045] In one embodiment of the present application, the phosphorus source may include, but is not limited to, one or more of NH4H2PO4, H3PO4, and (NH4)2HPO4. Specifically, the phosphorus source may be NH4H2PO4. In another embodiment of the present application, the phosphorus source may be (NH4)2HPO4 and H3PO4.

[0046] In one embodiment of the present application, the molar ratio of lithium in the lithium source, phosphorus in the phosphorus source, and metal in the metal source is (0.4-0.5): (1.4-1.6): 1. Specifically, the molar ratio of lithium in the lithium source, phosphorus in the phosphorus source, and metal in the metal source may be, but is not limited to, 0.4: 1.4: 1, 0.4.2: 1.42: 1, 0.45: 1.45: 1, 0.48: 1.48: 1, 0.45: 1.5: 1, 0.48: 1.55: 1 or 0.5: 1.6: 1, etc. In one embodiment of the present application, the molar ratio of lithium in the lithium source, phosphorus in the phosphorus source, and metal in the metal source may be (0.4-0.45): (1.4-1.55): 1. In another embodiment of the present application, the molar ratio of the lithium element in the lithium source, the phosphorus element in the phosphorus source, and the metal element in the metal element source can be (0.44-0.5):(1.5-1.6):1.

[0047] In one embodiment of the present application, a solid phase method is used to prepare a lithium ion solid electrolyte, wherein the metal element source can be a metal oxide, the lithium source can be a Li2CO3 solution, and the phosphorus source can be a (NH4)2HPO4 solution. The metal oxide weighed according to the stoichiometric ratio is ground, and the phosphorus source is added to form a mixed solution; the lithium source, the mixed solution and the core material solution are mixed, dried at 120°C, and sintered to obtain a lithium ion solid electrolyte.

[0048] In one embodiment of the present application, the metal oxides are proportioned according to a stoichiometric ratio, and the grinding time is 1h-6h. The metal oxides can be proportioned according to an equimolar ratio or a non-equimolar ratio. When the metal oxides are proportioned in a non-equimolar ratio, the molar percentage of each metal oxide is greater than or equal to 10% in terms of the metal oxide. Specifically, the grinding time can be, but is not limited to, 1h, 2h, 3h, 4h, 5h or 6h, etc. In one embodiment of the present application, the grinding time can be 1h-4h. In another embodiment of the present application, the grinding time can be 3h-6h. In some embodiments, zirconium oxide balls and / or aluminum oxide balls are added during grinding.

[0049] In one embodiment of the present application, a liquid phase method is used to prepare a lithium ion solid electrolyte, wherein the metal element source may be a metal organic alkoxide and a metal nitrate, the lithium source may be LiNO3, and the phosphorus source may be (NH4)2HPO4. The metal nitrate weighed in a stoichiometric ratio is added to water to form a metal nitrate solution; the lithium source and the phosphorus source are mixed, and water is added to form a lithium source-phosphorus source mixed solution; the metal organic alkoxide is added to ethanol to form a metal organic alkoxide solution; the core material solution, the metal nitrate solution, the lithium source-phosphorus source mixed solution and the metal organic alkoxide solution are uniformly mixed, dried at 120°C, and sintered to obtain a lithium ion solid electrolyte.

[0050] In one embodiment of the present application, the structural formula of the metal organic alkoxide is M'(OR)4, R is -(CH2) a CH3, the value of a is an integer between 0 and 6. Specifically, M' may be but not limited to Ti, Ge or V, and the value of a may be but not limited to 0, 1, 2, 3, 4, 5 or 6. In one embodiment of the present application, when M' is Ti and a is 2, the metal organic alkoxide may be Ti(O(CH2)2CH3)4. In another embodiment of the present application, when M' is Ge and a is 4, the metal organic alkoxide may be Ge(O(CH2)4CH3)4.

[0051] In one embodiment of the present application, the sintering temperature is 700°C-900°C, and a suitable sintering temperature is conducive to promoting the formation of a lithium salt solid electrolyte. Specifically, the sintering temperature may be, but is not limited to, 700°C, 750°C, 800°C, 850°C or 900°C. In one embodiment of the present application, the sintering temperature may be 700°C-850°C. In another embodiment of the present application, the sintering temperature may be 800°C-900°C.

[0052] The present application provides a battery, comprising a lithium ion solid electrolyte provided in any of the above embodiments or a lithium ion solid electrolyte prepared by the preparation method provided in any of the above embodiments. In one embodiment of the present application, the lithium ion solid electrolyte can be used in an electrolyte, a diaphragm and / or a positive electrode sheet, which can improve the ionic conductivity and structural stability of the battery. The lithium ion solid electrolyte provided in the present application has high ionic conductivity, high stability, and low water absorption, which is beneficial to improving the electrochemical performance and cycle life of the battery.

[0053] In one embodiment of the present application, the battery includes a positive electrode sheet and a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet. In one embodiment of the present application, the battery also includes an electrolyte. Among them, at least part of the positive electrode sheet and at least part of the negative electrode sheet are immersed in the electrolyte. The electrolyte of the present application is not particularly limited, and can be, but not limited to, various substances that can be used as battery electrolytes in the art.

[0054] The present application also provides an electrical device, which includes the battery described in any of the above embodiments. The electrical device provided by the present application has good cycle performance, high safety performance, and strong market competitiveness. Electrical equipment includes vehicles, electronic equipment, energy storage systems, etc., wherein the electronic equipment may include, for example, mobile phones, tablets, watches, VR glasses, etc. In one embodiment of the present application, the battery can be used in vehicles, which can increase the service life and charging rate of the vehicle, increase the widespread application of new energy vehicles, and facilitate the construction of a green and environmentally friendly environment. In another embodiment of the present application, the battery can also be used in mobile phones, which can reduce the preparation cost of the battery and improve the safety of battery use. The above-mentioned battery of the present application can be arranged in the electrical equipment in the form of a single cell, a battery module, a battery pack, etc.

[0055] The effect of the technical solution of the present application is further illustrated below through specific examples.

[0056] Example 1

[0057] A lithium ion solid-phase electrolyte is prepared by a liquid phase method, comprising mixing zirconium nitrate, lead nitrate, tin nitrate and manganese nitrate in a molar ratio of 1:1:1:1 with 500 ml of water, wherein the mass of zirconium nitrate is 34 g, the mass of lead nitrate is 33 g, the mass of tin nitrate is 36.6 g, and the mass of manganese nitrate is 25.1 g, to form a first metal element source solution, and dissolving 22.8 g of titanium ethoxide in 200 ml of ethanol to form a second metal element source solution;

[0058] 18.3 g of lithium source (Li2CO3) and 86.25 g of phosphorus source (NH4H2PO4) were added to 200 ml of water to form a lithium source-phosphorus source mixed solution;

[0059] 1000 g of core material (Li 1.3 Al 0.3 Ti 1.7 The powder of (PO4)3) is dispersed in 3000 g of water to obtain a core material solution;

[0060] The core material solution, the first metal element source solution, the second metal element source solution and the lithium source-phosphorus source mixed solution were mixed, stirred for 3 hours, dried at 120° C., and sintered at 800° C. in an oxygen atmosphere to obtain a lithium ion solid electrolyte;

[0061] The prepared lithium ion solid electrolyte was placed on a positive electrode active material (LiNi 0.8 Co 0.1 Mn 0.1O2), the mass percentage of lithium ion solid electrolyte is 2%, the negative electrode active material is graphite and electrolyte (lithium salt concentration is 1M LiPF6, the solvent is EC, DMC, DEC in a volume ratio of 1:1:1) to prepare a soft pack battery.

[0062] Example 2

[0063] The difference from Example 1 is that zirconium nitrate, lead nitrate and cerium nitrate in a molar ratio of 1:1:1 are mixed with 500 ml of water, wherein the mass of zirconium nitrate is 34 g, the mass of lead nitrate is 33 g, and the mass of cerium nitrate is 43.4 g, to form a first metal element source solution, and 22.8 g of titanium ethoxide is dissolved in 200 ml of ethanol to form a second metal element source solution;

[0064] 14.5 g of a lithium source (Li2CO3) and 69 g of a phosphorus source (NH4H2PO4) were added to 200 ml of water to form a lithium source-phosphorus source mixed solution.

[0065] Example 3

[0066] The difference from Example 1 is that zirconium nitrate, manganese nitrate and cerium nitrate in a molar ratio of 1:1:1 are mixed with 500 ml of water, wherein the mass of zirconium nitrate is 34 g, the mass of manganese nitrate is 25.1 g, and the mass of cerium nitrate is 43.4 g, to form a first metal element source solution, and 22.8 g of titanium ethoxide is dissolved in 200 ml of ethanol to form a second metal element source solution;

[0067] 14.5 g of lithium source (Li2CO3) and 69 g of phosphorus source (NH4H2PO4) were added to 200 ml of water to form a lithium source-phosphorus source mixed solution;

[0068] 1000 g of core material (Li 1.3 Al 0.5 Ge 1.5 The powder of (PO4)3) was dispersed in 3000 g of water to obtain a core material solution.

[0069] Example 4

[0070] The difference from Example 1 is that zirconium nitrate, manganese nitrate and lead nitrate in a molar ratio of 1:1:1 are mixed with 500 ml of water, wherein the mass of zirconium nitrate is 34 g, the mass of manganese nitrate is 25.1 g, and the mass of lead nitrate is 33.1 g, to form a first metal element source solution, and 22.8 g of titanium ethoxide is dissolved in 200 ml of ethanol to form a second metal element source solution;

[0071] 14.5 g of lithium source (Li2CO3) and 69 g of phosphorus source (NH4H2PO4) were added to 200 ml of water to form a lithium source-phosphorus source mixed solution;

[0072] 1000 g of core material (Li 1.3 Al 0.5 Ge 1.5 The powder of (PO4)3) was dispersed in 3000 g of water to obtain a core material solution.

[0073] Example 5

[0074] The difference from Example 1 is that zirconium nitrate, hafnium nitrate and cerium nitrate in a molar ratio of 1:1:1 are mixed with 500 ml of water, wherein the mass of zirconium nitrate is 34 g, the mass of hafnium nitrate is 42.7 g, and the mass of cerium nitrate is 43.4 g, to form a first metal element source solution, and 22.8 g of titanium ethoxide is dissolved in 200 ml of ethanol to form a second metal element source solution;

[0075] 14.5 g of lithium source (Li2CO3) and 69 g of phosphorus source (NH4H2PO4) were added to 200 ml of water to form a lithium source-phosphorus source mixed solution;

[0076] 2000 g of core material (Li 1.3 Al 0.3 Ti 1.7 The powder of (PO4)3) was dispersed in 6000 g of water to obtain a core material solution.

[0077] Example 6

[0078] The difference from Example 1 is that zirconium nitrate, hafnium nitrate and cerium nitrate in a molar ratio of 1:1:1 are mixed with 500 ml of water, wherein the mass of zirconium nitrate is 34 g, the mass of hafnium nitrate is 42.7 g, and the mass of cerium nitrate is 43.4 g, to form a first metal element source solution, and 22.8 g of titanium ethoxide is dissolved in 200 ml of ethanol to form a second metal element source solution;

[0079] 14.5 g of lithium source (Li2CO3) and 69 g of phosphorus source (NH4H2PO4) were added to 200 ml of water to form a lithium source-phosphorus source mixed solution;

[0080] 1000 g of core material (Li 1.3 Al 0.3 Ti 1.7 The powder of (PO4)3) was dispersed in 3000 g of water to obtain a core material solution.

[0081] Example 7

[0082] The difference from Example 1 is that zirconium nitrate, hafnium nitrate and cerium nitrate in a molar ratio of 1:1:1 are mixed with 500 ml of water, wherein the mass of zirconium nitrate is 34 g, the mass of hafnium nitrate is 42.7 g, and the mass of cerium nitrate is 43.4 g, to form a first metal element source solution, and 22.8 g of titanium ethoxide is dissolved in 200 ml of ethanol to form a second metal element source solution;

[0083] 14.5 g of lithium source (Li2CO3) and 69 g of phosphorus source (NH4H2PO4) were added to 200 ml of water to form a lithium source-phosphorus source mixed solution;

[0084] 500 g of core material (Li 1.3 Al 0.3 Ti 1.7 The powder of (PO4)3) was dispersed in 1500 g of water to obtain a core material solution.

[0085] Example 8

[0086] The difference from Example 1 is that zirconium nitrate, lead nitrate, tin nitrate and manganese nitrate in a molar ratio of 3:2:2.55:0.45 are mixed with 500 ml of water, wherein the mass of zirconium nitrate is 51 g, the mass of lead nitrate is 33 g, the mass of tin nitrate is 46.67 g, and the mass of manganese nitrate is 5.65 g, to form a first metal element source solution.

[0087] Example 9

[0088] The difference from Example 1 is that zirconium nitrate, lead nitrate and cerium nitrate in a molar ratio of 7:8:1 are mixed with 500 ml of water, wherein the mass of zirconium nitrate is 59.5 g, the mass of lead nitrate is 66.1 g, and the mass of cerium nitrate is 8.15 g, to form a first metal element source solution.

[0089] Comparative Example 1

[0090] The difference from Example 1 is that 500 g of the core material (Li 1.3 Al 0.3 Ti 1.7 The powder of (PO4)3) was dispersed in 2000 g of water to obtain a core material solution, which was stirred for 3 h, dried at 120° C., and sintered at 800° C. in an oxygen atmosphere to obtain a lithium ion solid electrolyte.

[0091] Comparative Example 2

[0092] The difference from Example 1 is that the first metal element source solution and the second metal element source solution are not added, a carbon source is added, and the coating layer is a carbon coating layer.

[0093] Comparative Example 3

[0094] The difference from Example 1 is that the first metal element source solution does not include zirconium nitrate and lead nitrate.

[0095] Comparative Example 4

[0096] The difference from Example 1 is that the first metal element source solution does not include zirconium nitrate, lead nitrate and tin nitrate.

[0097] Comparative Example 5

[0098] The difference from Example 1 is that the first metal element source solution is not added.

[0099] Comparative Example 6

[0100] The difference from Example 1 is that the first metal element source solution is zirconium nitrate, lead nitrate, tin nitrate and aluminum nitrate in a molar ratio of 1:1:1:1.

[0101] Performance Testing

[0102] The lithium ion solid electrolytes prepared in the above-mentioned embodiments 1-9 and comparative examples 1-6 were subjected to particle size testing. The testing process was as follows: using a wet particle size analyzer, the powder was dispersed in ethanol to perform a particle size distribution test, and the D50 in the test result was taken as the particle size of the lithium ion solid electrolyte. The powder was cut using a focused ion beam in a dual-beam electron microscope to obtain a cross section. An EDS line scan was performed on the cross section, and the core-shell boundary was determined based on the position where the line scan element mutated, and then the coating layer thickness and the particle size of the core were measured. The test results are shown in Table 1.

[0103] The lithium ion solid electrolytes prepared in the above Examples 1-9 and Comparative Examples 1-6 were subjected to X-ray diffraction test. The test process was as follows: using a Cu target, a voltage of 40 kV, a current of 40 mA, a 2θ angle range of 10°-80°, and a step size of 0.066° / s. Figure 2 The X-ray diffraction diagrams of the lithium ion solid electrolytes prepared in Examples 1-7 and Comparative Example 1 of the present application show that the lithium ion solid electrolytes prepared in Examples 1-7 have no impurity phase.

[0104] The lithium ion solid electrolytes prepared in the above examples 1-5 and comparative examples 1-3 were subjected to a water absorption test. The test process was as follows: 0.1 g of the lithium ion solid electrolyte was exposed to a -10°C dew point room for 24 hours using a coulometric moisture meter for testing. The test conditions were a temperature of 160°C and a time of 600 seconds to obtain its water content. The test results are shown in Table 2.

[0105] The lithium ion solid electrolytes prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-3 were subjected to ion conductivity tests. The test process was as follows: 0.5 g of lithium ion solid electrolyte powder was taken, pressed into a disc with a diameter of 12 mm, and sintered at 800° C. in an air atmosphere. The disc was taken out, gold was sprayed on the round surfaces at both ends, and it was sandwiched between two stainless steel sheets. The electrochemical impedance spectroscopy test was performed in a CR2032 button battery. The test frequency range was 5 MHz-1 Hz. In the obtained impedance spectrum, there was an arc in the high frequency region. The diameter of the arc was used as the R value for ion conductivity calculation. The ion conductivity was calculated using the following formula: σ=L / (R·A), where L is the thickness of the solid electrolyte sheet (cm), and A is the end surface area of ​​the solid electrolyte sheet (cm 2 )), R is the diameter of the high-frequency arc segment in the impedance spectrum (Ω). The test results are shown in Table 2. Figure 3 This is the electrochemical impedance spectrum of the lithium ion solid electrolyte sheet prepared in Example 1 of the present application. It can be seen that there is an arc position (arrow direction) in the high frequency region, and the diameter of the arc is used as the R value for calculating the ionic conductivity.

[0106] The lithium ion solid electrolytes prepared in the above Examples 1-9 and Comparative Examples 1-6 were tested for lithium dissolution. The test process was as follows: 3 g of the crushed powder was placed in 120 mL of deionized water and stirred for 2 h. The filtrate was filtered through a filter membrane and then subjected to ICP-AES test. The test results are shown in Table 2.

[0107] The batteries prepared in the above-mentioned Examples 1-9 and Comparative Examples 1-6 were subjected to rate and cycle performance tests. The test process was as follows: charge and discharge for 3 cycles at 0.33C, taking the discharge capacity of the last cycle as C, and then conducting rate and cycle tests. Capacity tests were conducted at 0.1C, 0.33C, 1C, 2C, and 3C rates, and the capacity retention rate was obtained after 500 cycles at 1C rate. The test results are shown in Table 3.

[0108] Table 1 Test results of lithium-ion solid electrolyte

[0109]

[0110]

[0111] Table 2 Test results of lithium-ion solid electrolyte

[0112]

[0113] Table 3 Battery test results

[0114]

[0115]

[0116] According to Examples 1-9 and Comparative Examples 1-6, it can be seen that the NASICON type lithium ion solid electrolyte provided by the present application not only maintains the high ionic conductivity of the traditional lithium ion solid electrolyte, but also reduces the hydrophilicity and water content of the lithium ion solid electrolyte. The obtained battery has good rate performance, excellent cycle performance, low preparation cost, and is conducive to the industrial application of the battery. According to Examples 1 and 2-9, it can be seen that suitable metal elements, suitable metal element molar ratios, and suitable preparation methods are all conducive to improving the ionic conductivity of the NASICON type lithium ion solid electrolyte and the diaphragm, reducing its water content, improving the rate performance of the battery, and reducing the internal resistance of the battery. According to Example 1 and Comparative Examples 1-6, it can be seen that the NASICON type lithium ion solid electrolyte with a core-shell structure provided by the present application, wherein the NASICON type solid electrolyte coating layer having at least four tetravalent metal elements can block the contact between the kernel and water, reduce the affinity and water content of the lithium ion solid electrolyte to water, improve the stability of the lithium ion solid electrolyte, and help improve the electrochemical performance of the battery.

[0117] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be noted that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A lithium ion solid electrolyte, characterized in that: The lithium-ion solid electrolyte includes a core and a coating layer coated on the surface of the core, the core includes a lithium-rich NASICON-type solid electrolyte, the coating layer includes a second NASICON-type solid electrolyte, the chemical formula of the second NASICON-type solid electrolyte is LiM2(PO4)3, and M is at least four tetravalent metal elements.

2. The lithium ion solid electrolyte according to claim 1, characterized in that The metal element is selected from Ti, Ge, Mn, In, Te, Sc, Y, V, Cr, Hf, Ce, Zr, Pb and Sn.

3. The lithium ion solid electrolyte according to claim 1 or 2, characterized in that Among the at least four tetravalent metal elements, the molar percentage of each of the metal elements is greater than or equal to 10%.

4. The lithium ion solid electrolyte according to any one of claims 1 to 3, characterized in that The lithium-rich NASICON solid electrolyte includes Li 1+a Al a Ti 2-a (PO4)3 and Li 1+y Al y Ge 2-y (PO4)3, wherein a is 0.1-0.5 and y is 0.1-0.

5.

5. The lithium ion solid electrolyte according to any one of claims 1 to 4, characterized in that The configuration entropy of the second NASICON-type solid-state electrolysis is greater than or equal to 10.73 J / (mol·K).

6. The lithium ion solid electrolyte according to any one of claims 1 to 5, characterized in that The coating layer has a thickness of 5nm-30nm, and the core has a D50 particle size of 100nm-5μm.

7. The lithium ion solid electrolyte according to any one of claims 1 to 6, characterized in that In the lithium ion solid electrolyte, the mass percentage of the coating layer is 5%-30%, and the mass percentage of the core is 70%-95%.

8. The lithium ion solid electrolyte according to any one of claims 1 to 7, characterized in that The ionic conductivity of the lithium ion solid electrolyte is greater than or equal to 4.8×10 -4 S / cm, and the water absorption of each gram of the lithium ion solid electrolyte is less than or equal to 0.25wt%.

9. A method for preparing a lithium ion solid electrolyte according to any one of claims 1 to 8, characterized in that: include: The metal element source, lithium source, phosphorus source and core material solution are mixed and sintered to obtain a lithium ion solid electrolyte.

10. The preparation method according to claim 9, characterized in that: The solid content of the core material solution is 5%-40%; The molar ratio of the lithium element in the lithium source, the phosphorus element in the phosphorus source and the metal element in the metal element source is (0.4-0.5):(1.4-1.6):

1.

11. The preparation method according to any one of claims 9 to 10, characterized in that: The metal element source includes one or more of metal nitrates, metal organic salts and metal oxides.

12. The preparation method according to any one of claims 9 to 11, characterized in that: The sintering temperature is 700°C-900°C.

13. A battery, characterized in that: The battery comprises the lithium ion solid electrolyte described in any one of claims 1 to 8 or the lithium ion solid electrolyte prepared by the preparation method described in any one of claims 9 to 12.

14. An electrical device, characterized in that: The electrical device comprises the battery according to claim 13.

Citation Information

Cited By

  • Surface modification method and application of high-nickel ternary positive electrode material

    CN120527389A